2001
DOI: 10.4049/jimmunol.166.7.4705
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mediators Released or Generated by IFN-γ-Treated Human Mast Cells Following Aggregation of FcγRI or FcεRI

Abstract: The high affinity receptor for IgG (FcγRI, CD64) is expressed on human mast cells, where it is up-regulated by IFN-γ and, thus, may allow mast cells to be recruited through IgG-dependent mechanisms in IFN-γ-rich tissue inflammation. However, the mediators produced by human mast cells after aggregation of FcγRI are incompletely described, and it is unknown whether these mediators are distinct from those produced after activation of human mast cells via FcεRI. Thus, we investigated the release of histamine and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 41 publications
2
80
0
2
Order By: Relevance
“…In vitro, Ag-specific IgG can cause human basophil/mast degranulation and release of mediators (29,30). The same mediators are released by both IgG-and IgE-mediated degranulation (30). Clinically, IgE-mediated and IgG-mediated reactions are virtually identical, and so whereas IgE-independent reactions used to be called anaphylactoid, both forms of the disease are now known as anaphylaxis (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, Ag-specific IgG can cause human basophil/mast degranulation and release of mediators (29,30). The same mediators are released by both IgG-and IgE-mediated degranulation (30). Clinically, IgE-mediated and IgG-mediated reactions are virtually identical, and so whereas IgE-independent reactions used to be called anaphylactoid, both forms of the disease are now known as anaphylaxis (31).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, Ag-specific IgG can cause human basophil/mast degranulation and release of mediators (29,30). The same mediators are released by both IgG-and IgE-mediated degranulation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Besides FceRI, basophils and mast cells also express activating FccR, which can promote degranulation (63). Indeed, FccRI-dependent degranulation of human mast cells mediated by antibodies of the IgG1 subclass is very similar to FceRI stimulation in regard to the amount and the pattern of released mediators (64,65). Thus, IgG production induced by 'infection' could also determine the outcome of anaphylaxis.…”
Section: Infections As Cofactors Of Anaphylaxismentioning
confidence: 99%
“…[4][5][6][7][8][9] However, it has become clear that rodent MCs are somewhat different from their human counterparts in terms of their sensitivity to some cytokines and drugs and their receptor expression profiles such as for Fc␥R. 3,[10][11][12][13] It is also observed that the level of IgE-dependent TNF-␣ production by human MCs is quite low compared to that by rodent MCs. 3,4,14 Therefore, it is now necessary to determine if human MCs express TLR4.…”
Section: Introductionmentioning
confidence: 99%
“…1 Among mediators, the production of Th2-type cytokines such as interleukin 5 (IL-5) and CC chemokines such as I-309 by human MCs is believed to be responsible for the initiation and maintenance of IgE-dependent allergic reactions. 2,3 Recent studies in animal models indicate that mouse MCs may play a protective role in host defense against bacteria through production of tumor necrosis factor ␣ (TNF-␣) as a result of mainly Toll-like receptor 4 (TLR4)-or CD48-mediated activation. [4][5][6][7][8][9] However, it has become clear that rodent MCs are somewhat different from their human counterparts in terms of their sensitivity to some cytokines and drugs and their receptor expression profiles such as for Fc␥R.…”
Section: Introductionmentioning
confidence: 99%